Apoptotic bone marrow-derived mononuclear cells accelerate liver regeneration after extended resection - N. A. Onishchenko; A. O. Nikolskaya; Z. Z. Gonikova; L. A. Kirsanova; M. Yu. Shagidulin; V. I. Sevastianov (Вестник трансплантологии и искусственных органов, 2022)
Objective: to compare the efficiency of regenerative processes in the liver using apoptotic bone marrow-derived mononuclear cells (BMMCs) and intact BMMCs from healthy animals on an extended liver resection (ELR) model.Materials and methods. Male Wistar rats (n = 77) with an ELR model (70–75%) were divided into 3 groups: group 1 (control with a single intraperitoneal injection of saline), group 2 (single intraperitoneal injection of unsorted intact BMMCs at a dose of 30–35 × 106, and group 3 (single intraperitoneal injection of apoptotic BMMCs at the same dose). Restoration of biochemical parameters of liver function and mass, as well as the emerging microstructural changes in hepatocytes in histological preparations, were monitored by assessing hepatocyte mitotic activity (MA) during the first 7–10 days after ELR.Results. It was found that in groups 2 and 3, as compared with group 1, there was no death after ELR modeling, and that the biochemical parameters of liver function normalized more rapidly (at days 10–14). Hepatocyte MA in group 3 sharply increased as early as on day 1, and mitotic index (MI) averaged 14‰, reaching 20.9‰ in some experiments; MI in the control group remained at the baseline by this time, while in group 2, MI was only 3.2‰. In group 3, liver mass recovered more rapidly after ELR to baseline values already at days 8–10, whereas the recovery was at day 12–14 and day 17–20 in group 2 and group 1, respectively. It was suggested that the more pronounced increase in the efficiency of regenerative processes in the liver after ELR in group 3 after using apoptotic BMMCs was due to the release from these cells of a large spectrum of formed paracrine factors, including various classes of RNA molecules involved in the regeneration process.Conclusion. Apoptotic BMMNCs have a more effective adaptive and regulatory potential than intact BMMCs because reorganizations are rapidly formed in the damaged liver cells, providing an early and more powerful activation of the targeted regenerative program.